Proceedings the 5th international conference for Asia Pasific Arts Studies (ICAPAS) graduate school of Indonesia Institute of Arts Yogyakarta October 17th, 2017 : technologies of art / editor, Kurniawan Adi Saputro - INTERNATIONAL CONFERENCE FOR ASIA PASIFIC ARTS STUDIES (ICAPAS) 5th : 2017 : Yogyakarta; KURNIAWAN ADI SAPUTRO (Graduate School of Indonesia Institute of Arts Yogyakarta)
191 halaman : ilustrasi, tabel, foto, grafik ; 29 cm.